# maths

posted by .

differentiate using product, chain and quotient rule

ln x / 5x-7

and

e^x / 2x^3 - 1

could you help me out with the first and just point me in the right direction for the first i cant seem to get the steps in the right order and then it gets all muddled

thank you

A!

• maths -

let u= e^x v=(5x-7)
du/dx=e^x dv/dx= 5
f= uv^-1
f'= u d(v^-1)/dx+ v^-1 du/dx

f'= -uv^-2 dv/dx + v^-1 e^x
so...

f'=-5e^x/(5x-7)^2+ e^x/(5x-7

check that.

## Similar Questions

1. ### Product Rule

Can someone please help me with this? f(x)=(x-2)^1/2 * (x^2-3)^3 find f'(x) using the product rul. This is what I came up with I just need to know if I did it right. f'(x)=(x-2)^1/2*3(x^2-3)+(x^2-3)^3*(1)^-1/2 Hopefully I did. Thanks.
2. ### Math - Chain Rule

I've been having some difficulities with this but I think I figured it out. Could you double check me and make sure I'm doing the correct steps?
3. ### math

can some one please help me with the following questions as i don't understand them please (a) write down the derivative of each of the functions f(x)=E7x and g(x)=cos(2x) using the product rule differentiate the function k(x)=E7xcos(2x) …
4. ### MoRe HeLp PlEaSe!! (calc)

Also can I get some help with this LONG, TIRESOME PROBLEM?
5. ### Math, Calculus

Find the derivative of the function. y= xcosx - sinx What's the derivative?
6. ### Calculus

How do I use the chain rule to find the derivative of square root(1-x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used?
7. ### calculus

I have been asked to solve this two different ways. The first way is to use the chain rule and then simplify (which I have already done properly), and the second way is to simplify and then differentiate (not necessarily with the chain …
8. ### calculus

Let z = ∫e^(sin(t))dt from x to y a = x b = y I tried thinking about it like a chain rule but even then i'm a little unsure. I know dz/dt = e^(sin(t)). Can you please point me in the right direction if i'm supposed to use the …
9. ### Calculus

I'm having problems with this one. Can't get the right answer. Differentiate the following using the chain rule. f(x) = squareroot(x^2+1)/(3x+1) I know that I can take the whole thing and put it to the (1/2) and differentiate that …